Business Communication in the Era of Artificial Intelligence: Opportunities and Challenges - M. Sholeh Awaludin; Havis Aravik (Penerbit dan Percetakan CV. Picmotiv, 2025)
This study aims to examine the transformation of business communication in the era of Artificial Intelligence (AI), focusing on the opportunities and challenges posed by AI in interpersonal communication. Employing a descriptive qualitative approach and thematic literature analysis, the study reveals that AI positively contributes to enhancing efficiency, personalization, and accessibility in business communication, including the use of virtual assistants and social media algorithms. On the other hand, significant challenges arise, such as the loss of emotional depth, AI’s limitations in understanding social context, and threats to communication authenticity. These findings underscore the need for ethical and strategic approaches in AI implementation to support inclusive and meaningful communication within modern business environments.